Advances in antibody discovery from human BCR repertoires - Xu, Zichang; Ismanto, Hendra S.; Zhou, Hao; Saputri, Dianita S.; Sugihara, Fuminori; Standley, Daron M. (Frontiers in Bioinformatics, 2022)
Antibodies, the soluble portion of B cell receptors (BCRs), make up an important and growing class of compounds used for the diagnosis or treatment of disease. While traditional antibody discovery utilized immunization of animals to generate lead compounds, technological innovations have made it possible to search for antibodies targeting a given antigen within the repertoires of B cells in humans. Here we group these innovations into four broad categories: cell sorting allows collection of cells enriched in specificity to one or more antigens; BCR sequencing can be performed on bulk mRNA, genomic DNA or on paired (heavy-light) mRNA; BCR repertoire analysis generally involves clustering BCRs into specificity groups or more in-depth modeling of antibody-antigen interactions, such as antibody-specific epitope prediction; validation of antibody-antigen interactions usually requires expression of antibodies, followed by antigen binding assays or epitope mapping. Together with innovations in Deep Learning these technologies will contribute to the future discovery of diagnostic and therapeutic antibodies directly from humans.